PENGARUH PELATIHAN, PENGEMBANGAN, SERTA MOTIVASI KERJA TERHADAP KINERJA KARYAWAN KOPERASI PRIMKOPPOL SUKOHARJO TAHUN 2022 - Purnomo, Khrisna Adhy; Rohwiyati, Rohwiyati; Sulistya, Sulistya (Universitas Of Surakarta, 2024)
The purpose of this study was to find out and analyze the effect of training, HR development, motivation on the performance of the Primkoppol Sukoharjo Cooperative employees in 2022. The method used in this study was the sampling method from the population, the object of this study was the Work of the Primkoppol Sukoharjo Cooperative Employees. Data were processed using SPSS by testing validity, reliability, classic assumption test, t test, F test, and R2 test. In this study, 21 respondents were used. The results of this study are training (X1) has a positive and significant effect on employee performance (Y) employee performance which is proven to be true, the t value is 11,866 > 1,920 and the significance value is 0.003 1,920 and a significance value of 0.006 1,920 and a significance value of 0,000 2.93 with a significance of 0.000